The Analysis of Factors that Influencing Mother's Knowledge Level on Basic Immunization - Fadly, Sul; Fitriani, Rini; Asriani (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Introduction: One of the goals of WHO formulated at the Atlanta meeting in 1978 was to achieve health for all by 2000. The purpose of this study is to describe the factors that influence the level of mother’s knowledge regarding basic immunization. Methods: The research was conducted in January - February 2020 in the Dahlia Health Center in Makassar. The sample was 80 mothers whose babies were immunized at the Dahlia Health Center. A purposive sampling method was used. The data collection method used was a survey questionnaire that was distributed to respondents. The data analysis used was a univariate data analysis using the SPSS. Results: The largest subjects were senior high school education and the smallest subjects were university education. Most of the subjects were housewives or unemployed (75%) and the least of the subjects were civil servants (3.75%). Most subjects in this study were aged 21-35 years old (53.75%) and the least subjects were under 20 years old (15%). All respondents were Muslim (100%). Most of the family environment factors that their family did not accompany them for immunization (53.75%) and community environmental factors that around people brought their children for immunization (100%). Conclusion: All factors of this study affect the mother’s knowledge but we can conclude that the most role influence of factors to knowledge mother were environment and religion.